THE IMPORTANCE OF EMPLOYEE ACTIVITY IN THE INNOVATIVE DEVELOPMENT OF CONSTRUCTION ORGANIZATIONS AND WAYS OF ITS INCREASE (Marketing Journal, 2025)
This article analyzes the content of our countryʼs innovation strategy and its implementation in construction, and also studies the interests and goals of construction organizations as an important element of the subjects of innovation activity. The author has studied the forms and directions of innovation activity in contracting construction organizations and developed proposals for their improvement.
Keywords: chain "industry -territory -science/higher education -organization"; innovation activity; innovative activity of employees; propensity to innovation